The Role of Civil Society Organizations in The Formulation of Presidential Regulation Number 7 of 2021 on Violent Extremism in Indonesia during the Period of 2020-2024 - Saryam, Tarikem; Ragamustari, Safendri Komara; Kurniawan, Novianto Budi (PCD Journal, 2023)
In January 2021, President Joko Widodo signed the National Action Plan for Preventing and Countering Violent Extremism that Leads to Terrorism (Presidential Regulation Number 7/2021). The increasing threats of violent extremism and terrorism make ratification of this policy urgent. The policy seeks to coordinate government and stakeholders against terrorism in Indonesia. The policy formulation demonstrates the resolve to engage the entire government and society. One of them is the roles of civil society organizations (CSOs). This study aims to describe the roles of the Wahid Foundation, C-SAVE, and Inklusif Foundation in formulating Presidential Regulation Number 7/2021. This qualitative study uses Arnstein's ladder participation as its conceptual framework. This study showed that the Wahid Foundation and the government are partners. In comparison, the C-SAVE and the Inklusif Foundation contribute to the level of tokenism. The Inklusif Foundation is only in the consultation or deliberation phase. However, despite the three CSOs having distinct work foci and levels of involvement, they have all contributed to the impetus behind the promulgation of this policy.